Structural and morphological tuning of dithienobenzodithiophene-core small molecules for efficient solution processed organic solar cells - Jung, Minwoo; Seo, Dongkyun; Kwak, Kyungwon; Kim, Ajeong; Cha, Wonsuk; Kim, Hyunjung; Yoon, Youngwoon; Ko, Min Jae; Lee, Doh-Kwon; Kim, Jin Young; Son, Hae Jung; Kim, BongSoo (ELSEVIER SCI LTD, 2015)
The fused dithieno[2,3-d:2',3'-d']benzo[1,2-b:4,5-b']dithiophene (DTBDT) structure was coupled with diketopyrrolopyrrole (DPP) moieties to generate highly planar bis(2,5-bis(2-ethylhexyl)-3,6-di(thiophen-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione)dithieno[2,3-d:2',3'-d]benzo[1,2-b:4,5-b']dithiophene (DTBDTDPP-EH) and bis(2,5-bis(2-butyloctyl)-3,6-di(thiophen-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione)dithieno[2,3-d:2',3'-d']benzo[1,2-b:4,5-b']dithiophene (DTBDTDPP-BO) molecules, where the EH and BO stands for 2-ethylhexyl and 2-butyloctyl groups respectively. The morphology of the DTBDTDPP-EH alone or DTBDTDPP-EH:[6,6]-phenyl-C-61-butyric acid methyl ester (PCBM) blend film was controlled using post-thermal annealing at 130 degrees C or addition of 1,8-diiodooctane (DIO) additives. The DIO-additive treatment was more effective than thermal annealing at increasing crystallinity; the DIOadditives promoted the formation of nanoscopically well-connected molecular crystalline domains in the blend films. This observation well explained the ordering of the photovoltaic properties of DTBDTDPP-EH:PCBM devices: from worst to best, as-cast, thermally treated, and DIO-treated photoactive films. The DTBDTDPP-BO:PCBM device followed the similar trend with lower performances due to the presence of irregularly overgrown domains. Overall, we demonstrate that it is critical to optimize nanoscale film morphologies by engineering alkyl chains and selecting an appropriate processing method. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: HIGH PHOTOVOLTAIC EFFICIENCY; LOW-BANDGAP POLYMERS; DIKETOPYRROLOPYRROLE; PERFORMANCE; BENZODITHIOPHENE; UNIT; AGGREGATION; ADDITIVES; CATHODE